Proper Name Structures in the Sundanese Community: Onomastic Studies - Nunung Sitaresmi; Encep Kusumah; Novi Resmini; Rahmawati Rahmawati; Johari Johari (Universitas Muhammadiyah Malang, 2025)
Sundanese society, as the second largest ethnic group in Indonesia, has distinctive proper names to distinguish itself from other ethnic communities. This study aims to describe the structure and function of proper names in Sundanese society. This research uses qualitative methods with theoretical onomastics, phonetics, and morphology approaches. Data in proper names was sourced from the YouTube channel Fiksi with the title “Sundanese Names mah Unik Pisan | Fiksi,” published on April 9, 2020. The data were collected by downloading and recording. The findings of this study consist of four main points. First, Sundanese proper names generally follow open syllable patterns, such as two syllables + 3 syllables and two + 4 syllables. Second, first names are a form of partial or complete repetition, either from the last name’s first, middle, or last syllable. Third, proper names tend to use high and low vowels. Fourth, proper names function as (1) identity markers, (2) easy-to-pronounce, and (3) easy-to-recall. In conclusion, proper names in the Sundanese community have unique structural patterns and functions, strengthening their role as cultural identity markers in Sundanese ethnic groups.